Surgical anatomy of sigmoid sinus with evaluation of its venous dominance for advances in preoperative planning - Zhu, Chunran; Chong, Yulong; Jiang, Chenjun; Xu, Wu; Wang, Jing; Jiang, Chengrong; Liang, Weibang; Wang, Bei (Frontiers in Neuroscience, 2023)
Microvascular decompression (MVD) is a widely adopted neurosurgery in treating cranial nerve diseases providing long-term pain relief. Improving surgical techniques has been a focus of recent studies. Venous structures such as the sigmoid sinus are essential to protect, and whose risk of destruction during surgery increases with size. The medical records of patients who went through MRI ahead of MVD surgery between Dec 2020 and Dec 2021 were reviewed. Section area of sigmoid sinus calculated from the MRI plane of auditory nerve showed a right dominance of the sinus. The improved method concerning the relationship between affected side and the dominant sigmoid sinus offered a better bone window and surgical field by planning the operation incision in advance. Intraoperative adjustment of the bone flap was avoided, and the risk of destructing the sigmoid sinus was reduced.